Influence of the COVID-19 Outbreak on Disease Activity and Quality of Life in Inflammatory Bowel Disease Patients - Conti, Chiara; Rosa, Ilenia; Zito, Luigia; Grossi, Laurino; Efthymakis, Konstantinos; Neri, Matteo; Porcelli, Piero (Frontiers in Psychiatry, 2021)
Objective: The present preliminary cross-sectional study aimed to investigate the extent to which health-related quality of life of patients with inflammatory bowel disease (IBD) was influenced by the outbreak of Covid-19 while controlling for disease activity. Methods: Two samples of 195 (recruited before Covid-19 outbreak) and 707 patients (recruited during the Covid-19-related lockdown) were included. Psychological distress (Hospital Anxiety and Depression Scale, HADS), quality of life (Inflammatory Bowel Disease Questionnaire, IBDQ), and somatization (Patient Health Questionnaire, PHQ-12) were concurrently assessed. Results: Patients with active IBD were more prevalently affected by ulcerative colitis (60.2%, η2=0.12) and, expectedly, showed higher psychological distress (HADS, d=0.34) and somatization (PHQ-12, d=0.39), as well as poorer disease-specific health-related quality of life (effect sizes for the total and subscale IBDQ scores in the large range of d>0.50). Hierarchical regression models revealed that setting (pre-Covid-19 outbreak vs. during lockdown) (p<.001) explained only a small portion (8%) of the IBDQ variance. IBD-related factors (ulcerative colitis and disease activity) and psychological factors (psychological distress and somatization) added a significant amount of 25% and 27%, respectively, to the explained IBDQ variance. The final model predicted 59% of the explained IBDQ variance. Conclusion: Clinical and psychological manifestations seem to be major impairments in IBD patients both before and during the Covid-19 outbreak. Furthermore, the quality of life of IBD patients seem to be more influenced by psychological and somatizing distressing symptoms than the pandemic-related living conditions.